Particulate composite surface by TIG torch surfacing - Maleque, Md. Abdul (2017)
The particulate composite surfaces have been developed in thick surface layers on a low alloy steels by preplacing different ceramic carbide particles into a shallow melt pool produced on a moving sample using traditional TIG torch melting technique. Surface layers ranging in thickness from 0.05 to 1.0 mm are formed, the thickness being determined by the process variables of heat input, particles feed rate and gas flow rate. Typical operating conditions employ TIG input energies, preplaced particle amount, gas flow rate and working distance. The composite surface was investigated by a diversity of techniques, including optical microscopy, scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD) and Microhardness testing.